A regulatory perspective on missing data in the aftermath of the NRC report. (17th December 2015) - LaVange, Lisa M.; Permutt, Thomas
Abstract : The issuance of a report in 2010 by the National Research Council (NRC) of the National Academy of Sciences entitled 'The Prevention and Treatment of Missing Data in Clinical Trials, ' commissioned by the US Food and Drug Administration, had an immediate impact on the way that statisticians and clinical researchers in both industry and regulatory agencies think about the missing data problem. We believe that there is currently great potential to improve study quality and interpretability—by reducing the amount of missing data through changes in trial design and conduct and by planning and conducting analyses that better account for the missing information. Here, we describe our view on some of the recommendations in the report and suggest ways in which these recommendations can be incorporated into new or ongoing clinical trials in order to improve their chance of success. Published 2015. This article is a U.S. Government work and is in the public domain in the USA.